Philosophy of Education in the Digital Age from the Perspective of Kolb's Experiential Learning Theory - امین, م.م. هەوار عومەر فەقێ ئەمین (Sulaimani Journal for Humanities, 2025)
The philosophy of education in the digital era presents a fundamental transformation in teaching and learning approaches, highlighting the importance of implementing Kolb's experiential learning theory as a solution for adapting educational systems to the needs of the modern era. Kolb's experiential learning theory identifies four systematic stages for the learning process: concrete experience, reflective observation, abstract conceptualization, and active experimentation. Within the framework of the digital era, these stages provide opportunities for innovation in implementation, resulting in the creation of an opportunity-rich environment where learners can acquire appropriate and relevant experience. The main problem of this research lies in the lack of studies on how to adapt learning theories with new digital tools, despite the widespread use of digital technology in education. The primary objective of this research is to attempt to answer the question: How can Kolb's experiential learning theory be used as a foundation for developing the philosophy of education in the digital era? Methodologically, this research conducted a theoretical analysis of technology use according to Kolb's theory and the importance of technology in learning stages. The research findings reveal that Kolb's theory provides a comprehensive framework for learning and knowledge acquisition through the use of digital technology, thereby developing the ability to create engaging learning experiences and increasing learners' skills in thinking, problem-solving, and sound decision-making. However, it is important to know that technology is merely a tool, and success depends on proper planning and implementation.
Keywords: Philosophy of Education; Digital Age; Learning Theory Technology Experience; Learning Experience